Reconciliação dinâmica de dados baseada em estimadores em uma malha de controle MPC - Silva, Guilherme Moura Afonso da (2017)
The data reconciliation in process control is extremely important regarding the industries because from this it is possible to obtain a greater efficiency in the performance in industrial process control meshes aiming at a lower cost and a higher quality of the product. In this work we approach data estimation techniques for the implementation of an online dynamic data reconciliation system in order to reduce the noise and the measurement uncertainties that are submitted in the process variables. The techniques used here are: the Kalman Filter, the Preditor-Corrector DDR Algorithm, the Moving Horizon Estimator (MHE) and the Constrained Extended Kalman Filter (CEKF). The analysis is performed by applying the dynamic data reconciliation system in a simulated process, characteristic of the chemical industry, operating under MPC (Model Predictive Control). The performance of the MPC controller is also enhanced by the use of the reconciled data in the feedback control loop.